Effect of low-flow oxygen therapy on 6MWD in PAH and CTEPH: a randomized non-inferiority crossover trial - Carmen Wick; Mona Lichtblau; Anna Titz; Julian Müller; Alessandro Vella; Zoe Bousraou; Michael Furian; Stéphanie Saxer; Esther I Schwarz; Silvia Ulrich (European Heart Journal Open, 2026)
Abstract Background Patients with pulmonary arterial and distal chronic thromboembolic pulmonary hypertension (PAH/CTEPH) frequently experience exertional dyspnea with desaturation. Although ambulatory low-flow supplemental oxygen therapy (SOT) is commonly prescribed, its effect via portable concentrators in daily life has not been studied. We investigated the effect of ambulatory SOT on six-minute walk distance (6MWD). Method This was a randomized non-inferiority cross-over study in patients with PAH or CTEPH desaturating by >3% during exercise. Patients performed two 6MWD tests in randomized order: one in ambient air and one with pulsed low-flow (1-2 l/min) nasal supplemental oxygen (SOT) by a portable back-packed concentrator. The primary outcome was 6MWD with a pre-defined non-inferiority margin of -35m for ambient air vs. SOT. Results Forty patients (age 62±15 years, 21 female, 20 PAH, 20 CTEPH) were included. The mean difference in 6MWD between ambient air and SOT was 0 m (95% CI: –15 to 14 m, p <0.001).Five patients exceeded the minimal clinically important difference of 35 m with SOT. At end-exercise, the cohort desaturated 2 % less with SOT (95% CI -3 to -0.2 %, p=0.025) and reported 1 point less dyspnea (95% CI 0.3 to 1, p<0.002). These effects were also observed in PAH but not in CTEPH. Conclusion Walking on ambient air was non-inferior to low-flow SOT during 6MWD in treated PAH/CTEPH patients with exercise-induced desaturation and relatively preserved exercise capacity. SOT reduced dyspnea in PAH. Future research should identify SOT responders and develop lighter, more effective devices tailored to patient needs. Registration: ClinicalTrials.gov (NCT06384534)